Pengaruh Temperatur dengan Tingkat Berbeda terhadap Konsumsi dan Perfoman Ayam Broiler - Aditya Pamungkas (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
This study aims to analyze the effect of environmental temperature on feed intake and performance in broiler chickens. The study was conducted using 200 Cobb 500 broiler chickens divided into four temperature treatment groups: P1 (gradual temperature decrease from 32-34°C to 20-24°C), P2 (stable temperature at 28-30°C), P3 (natural temperature fluctuations), and P0 (control). The parameters measured included feed intake, weight gain, and feed conversion ratio (FCR) of broiler chickens. The results showed that temperature significantly affected (p<0.05) feed intake, weight gain, and FCR. The conclusion of this study is the importance of stable broiler house temperature management to optimize broiler chicken productivity. This study recommends the application of climate control technology and feed formula adjustments as thermal stress mitigation strategies, particularly in tropical regions with high daily temperature variations.